Phase Transition in Di-oleoylphosphatidylglycerol/Monoolein Membranes due to Interactions of Positively Charged Peptides at their Lipid Membrane-Interface - Masum, Shah Md; Yamazaki, Masahito (Bangladesh Journal of Scientific and Industrial Research, 2010)
To elucidate the factors that induce phase transitions in biomembranes due to interactions of proteins/peptides at the lipid membrane-interface, the effects of positively charged peptides on the cubic phase (Q229) of Dioleoylphosphatidylglycerol (DOPG)/Monoolein (MO) membranes were investigated. Small angle X-ray Scattering (SAXS) results revealed that 12 mol% DOPG/88 mol % MO membranes in excess water at 25°C is body centered cubic phase of crystallographic space group Im3m (Q229). In presence of peptide LLKKK, the lattices constant of Q229 phase was gradually decreased with an increase of peptide concentration and a phase transition from cubic (Q229) to cubic (Q224) phase occurred at R=0.080; (R= molar ratio of peptide to lipid). On the other hand the designed peptide WLFLLKKK and antimicrobial peptide Magainin-2 induced lamellar phase (Lα) in the same mixture membranes. These results indicate that the interactions of the these peptides with this mixture membrane are different: LLKKK induces electrostatic attractive interactions and that of WLFLLKKKK and Magainin-2 bound with the lipid membranes induce electrostatic repulsive interaction at the membrane-interface, might be the major factor inducing different phase transitions in 12 mol% DOPG/88mol% MO mixture membranes. Key words: Antimicrobial peptide Magain-2; Dioleoylphosphatidylglycerol; Monoolein; Cubic phases; Small angle X-ray Scattering DOI: 10.3329/bjsir.v45i3.6530 Bangladesh J. Sci. Ind. Res. 45(3), 219-224, 2010